Interpretations and Comparisons of Pedestrian Movement and Land Use Activities in Kadıköy Region Using Space Syntax Method - Özkan Özbek, Müge; Ertürk, Fatma; Çelebi, T. Tacihan; Kınacı, Yagmur; Yücel Caymaz, Gökçen Firdevs (Street Art & Urban Creativity, 2022)
Prevailing theories of urban form suggest that pedestrian movement characterizes land uses, which in turn take advantage of ’natural movement’ generated by the grid configuration. The present paper investigated a configurational method of the urban grid for transit movement and as the main generator of movement patterns. A morphological method, namely space syntax analysis, was employed in the Kadıköy region, with an aim to understand, how the pedestrian movement was generated via a vis the urban layout. Axial analyses include defining the central cores of the settlement and determining the most intense movement in those centers, whereas segment analysis determines the scales and limits of the movement towards the points in such centers. Accordingly, axial maps were developed and analyzed in order to forecast the general functioning of Kadıköy grid. Measures of ‘axial integration’ for properties of the grid and segment analyses in micro-spatial characteristics of Kadıköy were used to investigate transit movement with an aim to gain an insight into movement patterns. Furthermore, correlation of segment and axial analyses were also performed to better simulate the movement. The present paper aimed to investigate the density of pedestrian movement by the characteristics and syntactic properties of urban space that identified limitations in the prediction of movement.